EFL students’ anxiety in writing journal manuscripts: An analysis of levels and causes - Ulya, Inayatul; Matra, Sarlita Dewi; Sidqi, Muhammad Fajru (Universitas Islam Sultan Agung, 2025)
Writing anxiety represents a critical affective variable in English as EFL academic context, associated with challenges in written language production. This study investigates the writing anxiety experienced by Indonesian EFL students, specifically examining its levels and underlying causes. Writing anxiety is a prevalent barrier to effective written expression, particularly in second language academic contexts. Employing a mixed-method approach, the research integrated both quantitative and qualitative data to provide a comprehensive understanding of this phenomenon. A purposive sample of 58 sixth-semester students from the English Language Education at Pekalongan University (UNIKAL) Central Java, Indonesia, was selected, focusing specifically on those who passed the Writing for Academic Purpose course. Data were collected using a questionnaire adapted from the Second Language Writing Anxiety Inventory (SLWAI) and supported by semi-structured interviews. The questionnaire measured three types of writing anxiety: cognitive, somatic, and avoidance behavior. Results revealed moderate levels of cognitive anxiety (M = 2.68), somatic anxiety (M = 2.81), and avoidance behavior (M = 2.83). Students expressed concerns about negative judgment, fear of making errors, and physical symptoms such as tension under time constraints—factors that contributed to procrastination and avoidance. Qualitative findings echoed these results, identifying fear of evaluation, limited writing experience, and low self-confidence as major contributors to writing anxiety. Notably, although students perceived writing tasks as challenging, their anxiety levels remained moderate, indicating a persistent but manageable affective barrier. It is recommended that future researchers and educators consider addressing cognitive, somatic, and behavioral dimensions of writing anxiety when designing EFL writing instruction, particularly by incorporating strategies that reduce fear of evaluation and build students’ writing confidence.